Exploring the Role of Ethics and Accountability in Enhancing Organizational Performance: The Moderating Influence of Perceived Organizational Support in the Public Sector - Kazeem Adebayo Oladimeji (Universitas Sultan Ageng Tirtayasa, 2024)
This study examines the impact of ethics and accountability on organizational performance in the public sector, with a specific focus on the moderating role of perceived organizational support. The research was conducted in the context of civil servants in Kwara State, Nigeria. The study employs a questionnaire-based survey administered to 165 civil servants, and data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings of the study reveal that both ethics and accountability have a significant positive influence on organizational performance. Furthermore, perceived organizational support was found to moderate the relationship between ethics, accountability, and organizational performance. Specifically, when employees perceive higher levels of support from their organization, the positive impact of ethics and accountability on performance is strengthened. These findings have important implications for public sector organizations. To enhance organizational performance, organizations should prioritize the promotion of ethical behavior and accountability through the establishment of ethical codes, training programs, and accountability mechanisms. Additionally, organizations should strive to create a supportive work environment by providing resources, and opportunities for development, and demonstrating genuine concern for employees' well-being. This study contributes to the existing literature by providing empirical evidence of the significant role of ethics, accountability, and perceived organizational support in driving organizational performance in the public sector.